Faktor-faktor yang Mempengaruhi PenurunanTulang Marginal Pada Awal Pemasangan Implan Dental - Rinda; Ariesanti, Yessy (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: A dental implant is a prosthetic or alloplastic material, which is embedded in the bone, to maintain retention and support for fixed or removable dental prosthetics. One of the challenging obstacles in dental implant treatment is marginal bone resorption. Early marginal bone loss (MBL) is a non-infective remodelling process of variable entity occurring within the first year after implant placement. It has a multifactorial etiology, being influenced by both surgical and prosthetic factors. Marginal bone loss is an important indicator to determine long term success of implant treatment. Radiographic evaluation are very renowned way to assess the longitudinal bone attachment to the implant. Case report : A 32 -year-old female patient came to RSGM USAKTI with a chief complaint of missing lower right posterior teeth 15 years ago due to big caries. Patient wanted to replace with implant. Comprehensive evaluation, like CBCT was done to make sure that she was indicated for dental implant. Insertion of BTK implant was done on the first phase of surgery. Implant was left for 3 months for osseointegration. Radiographic evaluation of the second phase of surgery there was a bone resorption about 2- 4 mm, but no mobililty, no signs of inflammation and no pain. In this case, Initial bone resorption diagnosis is essential because it gives the clinician a guideline for the necessity of corrective and preventive treatments. Conclusion: maintenance of gingival health around implant is important for decreasing bone loss.